Factor C*, the specific initiation component of the mouse RNA polymerase I holoenzyme, is inactivated early in the transcription process. - Brun, R P (1994)
Factor C* is the component of the RNA polymerase I holoenzyme (factor C) that allows specific transcriptional initiation on a factor D (SL1)- and UBF-activated rRNA gene promoter. The in vitro transcriptional capacity of a preincubated rDNA promoter complex becomes exhausted very rapidly upon initiation of transcription. This is due to the rapid depletion of C* activity. In contrast, C* activity is not unstable in the absence of transcription, even in the presence of nucleoside triphosphates (NTPs). By using 3'dNTPs to specifically halt elongation, C* is seen to remain active through transcription complex assembly, initiation, and the first approximately 37 nucleotides of elongation, but it is inactivated before synthesis proceeds beyond approximately 40 nucleotides. When elongation is halted before this critical distance, the C* remains active and on that template complex, greatly extending the kinetics of transcription and generating manyfold more transcripts than would have been synthesized if elongation had proceeded past the critical distance where C* is inactivated. In complementary in vivo analysis under conditions where C* activity is not replenished, C* activity becomes depleted from cells, but this also occurs only when there is ongoing rDNA transcription. Thus, both in vitro and in vivo, the specific initiation-conferring component of the RNA polymerase I holoenzyme is used stoichiometrically in the transcription process.